REDUCING SOCIAL STRATIFICATION VIA DIGITAL SKILLS IMPROVEMENT: THE CASE OF SOCIAL ENTERPRISES IN LATVIA - Casno, Kristīne; Sloka, Biruta (University of Zagreb, 2021)
Latvian social enterprises and social entrepreneurship are becoming important since the adoption of the Social Enterprise Law in 2017 (effective as of 01.04.2018). The number of social enterprises with the legal status and the number of financial grants awarded to social enterprises has been steadily increasing, reaching 161 and 110 of them have received support over 7 million EUR as of 28.02.2021, data of the Register of Social Enterprises. Covid-19 crisis is continuing to have a negative effect on the sector since Latvian social enterprises were not provided any complementary support despite the double-bottom lines they are achieving. Inability to provide structured support mechanisms in place for social enterprises may have a negative effect on their ability to achieve their social mission, thus diminishing their capabilities to minimize social stratification within Latvian society. In the face of crises, such as Covid-19, digital skills are of utmost importance as often the only way for social enterprises to continue operations, achieve their social goals and remain financially sustainable is to fully embrace the digital environment. While some enterprises are better at embracing the digital environment, others find it more challenging. The purpose of the study is to investigate the activities of Latvian work integration social enterprises in the digital environment and search for effective solutions for strengthening their digital capacity. Tasks - (1) analyze existing research (2) analyze social enterprise level of activity in the digital environment (3) investigate social enterprise management needs for digital skills improvement. Primary research methods – analysis of social enterprise activities in the Internet and social networks, interviews of management of social enterprises on digital skills improvement options. Research results indicate a need to invest concentrated efforts towards supporting the social enterprises at their initial entry into the digital environment.
Keywords: social entrepreneurship; social enterprise; social inclusion; social stratification; digital skills